KARAKTERISASI PANEL SEL SURYA 100 WP UNTUK SUMBER ENERGI WIRELESS SENSOR DI LAPANGAN - Qomaruddin Qomaruddin; Andi Setiono; Moh. Imam Afandi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Portable energy source is still limited by infrastructure and natural conditions for application in the field. The instrumentation system consists of several sensors requiring mobile and portable energy sources to support the multiple sensors on applications in the field. The energy source solar cells is one of the many sources of energy are already-established and simple installation. This study aimed to characterize the solar panels as 100 WP a portable and mobile energy sources. The method is measure the currents (Ampere) and voltage (Volt) output during  a daylight start at morning to evening, ie at 08:00 to 17:00 local time. With a several supporting components, characterization results shows that the solar panel system is capable of generating power that needed of the load. Load power consumption is 24,66 W and the peak energy generated is 68,54 W, so that the surplus energy will be stored in the accumulator and used a whole night.Keywords: characterization, solar cell 100 wp, energy sources.